Modulação da reação de hipersensibilidade tipo I por células apresentadoras de antígenos de camundongos tratados com Propionibacterium acnes ou seu polissacarídeo solúvel - Squaiella-Baptistão, Carla Cristina [UNIFESP] (2009)
Among Propionibacterium acnes (P. acnes) immunomodulatory effects, one of great importance, verified in our laboratory in a murine model of type I hypersensitivity to ovalbumin (OVA), is its capacity to direct the immune response to Th1 or Th2, depending on the animals treatment. Similar effect was induced by the soluble polysaccharide extracted from the bacteria (PS), however, since only its capacity to modulate the Th1 response has been verified, we decided to investigate, in the present study, if PS could also potentiate the Th2 response. In fact, this compound was able to potentiate or suppress the immediate hypersensitivity reaction in mice, depending on the protocol used. Besides, we investigated, in this work, whether the number of spleen cells and peritoneal B1 lymphocytes would be different between the treatment protocols, being related to potentiation or suppression of the OVA response, and also if the activation status of antigen presenting cells (APCs) and B1 lymphocytes could interfere on reaction modulation. We verified that the higher numbers of APCs expressing co-stimulatory molecules and the higher expression levels of these molecules on cell surface are probably related to potentiation of the Th2 response to OVA induced by P. acnes or PS. The higher CD80 expression by peritoneal B1c lymphocytes is also possibly involved with OVA response exacerbation in these animals. Besides, there seems to be a correlation between higher number of APCs expressing TLR4 and exacerbation of the immediate hypersensitivity reaction in P. acnes- or PS-treated mice. Differences on TLRs expression by spleen and peritoneal B1 lymphocytes can also be related to the type I hypersensitivity modulation. Analysis of cytokines synthesis by spleen APCs confirmed the Th2 potentiation or suppression in this model. Finally, in vitro experiments using co-cultures of dendritic cells and T lymphocytes indicated that P. acnes and PS seem to perform their effects of Th2 response potentiation or suppression by direct action on antigen presenting cells.